Balance Sheets and Debt Crises : Empirical Regularities for Modern Cases of Sovereign Distress - Meyer-Cirkel, Alexis (IMF Working Papers; Working Paper ;, 2021)
Public and private sector balance sheets are an important component to any analysis of debt sustainability. A vulnerable and indebted private sector can become a sudden liability for the government; alternatively, resilient household and bank balance sheets may reveal potential sources of funding for the sovereign during times of fiscal distress. In this paper, we document empirical regularities in the behavior of macroeconomic variables during debt crises, and show how both macroeconomic fundamentals and sectoral net worth can affect the likelihood of undergoing default.